PATRIZIA DI MONTE, YANNIS EFTHYMIOU, VERENA LENNA, VILY MYLONA, ALESSANDRA QUARTA, ANTONIO VERCELLONE, GIANNIS ZGERAS - Tools for the Generative Commons. Practices, processes and design - Kapstein, Paula (ZARCH, 2024)
PATRIZIA DI MONTE, YANNIS EFTHYMIOU, VERENA LENNA, VILY MYLONA, ALESSANDRA QUARTA, ANTONIO VERCELLONE, GIANNIS ZGERAS Tools for the Generative Commons. Practices, processes and design Generative Commons House, Saint Gilles, Bélgica, 2022, 321 pp. Tapa blanda Idioma: Inglés ISBN: 978-2-9602994-0-3